Structure and magnetic behavior of Zn doped NdMnO3 manganite: Neutron diffraction study. Issue 17 (1st December 2017) - Vyas, Brinda; Kundalia, Hetal; Udeshi, Malay; Trivedi, Priyanka; Vagadia, Megha; Rayaprol, S.; Kuberkar, D.G.
Abstract: Effect of Zn doping on the structural and magnetic properties of NdMnO3 has been investigated by neutron diffraction and dc magnetic susceptibility measurements. The partial replacement of Mn 3+ by Zn 2+ results in the decrease in TN . In the temperature dependent magnetization measurements, a broad hump and a sharp peak has been observed around 50 K and 10 K respectively for both the samples. Thermal hysteresis in magnetization between cooling and heating runs indicate first-order phase transition. Magnetization measurements on NdMn0.95 Zn0.05 O3 sample clearly show that, 5% Zn-doping in NdMnO3 results in the suppression in magnetism which is evident from the weakening of Nd–Mn interaction below TN, and resulting in antiferromagnetic coupling of Mn 3+ ions along x-axis with Mn 3+ moments oriented parallel or antiparallel to the x-component of Nd 3+ moments.